Analisis Keberlangsungan Sanksi Ekonomi Uni Eropa Terhadap Rusia Yang Dianggap Menganeksasi Krimea Periode 2014-2019 - Fahmi, Salma Afiqa; Utomo, Tri Cahyo (Journal of International Relations, 2020)
Crimea is an area that has been led by many countries, but since 1954 Crimea was given to Ukraine. After the collapse of the Soviet Union, Russia has been trying to take over Crimea so that it could return to Russia. This finally happened after the chaos in Ukraine appeared in 2013, which was caused by the Ukrainian leader that he would suspend talks on the Association Agreement. Utilizing the chaos, in early 2014 there was a sudden referendum in Crimea. The result of the referendum that the Crimean people’s wanted to join Russia received a lot of criticism because it was considered violating international law so it considered annexing Crimea. The European Union then imposed economic sanctions on Russia in 2014. The purpose of this study is to find out the reasons why the European Union still maintains economic sanctions even though they do not have a large impact on Russia. This research is explanative type research and is classified as qualitative research using the Congruence Analysis method through literature study. To analyze the case, the concepts of identity and norms in the theory of constructivism will be used. The results of this study indicate that the reasons behind the EU economic sanctions are still maintained because Russia has not fully implemented the Minsk Agreement and the interests of the European Union uphold their commitment to identity as an organization committed to peace. However, EU economic sanctions do not have a big impact on Russia because EU member states still depend on oil and gas from Russia, so economic sanctions are only in the form of restrictions. This needs to be further evaluated by the European Union so that sanctions can be effective and make Russia change its policy towards Crimea.